Dynamics of Sports Diplomacy in Promoting International Relations and Peace-Building - Acharya, Abinav (Political Science Journal, 2024)
In the ever-changing landscape of international relations, sports diplomacy is positioned to shine as a dynamic and influential tool, facilitating connections and nurturing mutual understanding among nations. This research aims in analyzing the relationship between sports and diplomacy, investigating how the unifying appeal of sports can cultivate cultural exchange, forge people-to-people connections, and foster peaceful coexistence. It evaluates the role of sports diplomacy in creating significant strides toward fortifying international stability. This research adopts a case study approach and comparative review to analyze sports diplomacy initiatives. It conducts qualitative assessments of key diplomatic events, all to gain a nuanced grasp of how sports can effectively drive positive international interactions. Historic events achieved through sports diplomacy are explored using qualitative analysis methods. The research is analytical and based on secondary sources of data. The scope of research includes contemporary developments and hurdles in sports diplomacy. The significance of this study lies in its potential contribution to the evolving landscape of diplomatic discourse, spotlighting the capacity of non-traditional actors and innovative approaches to diplomacy. Successful sports-driven case-studies are examined, illuminating the prospective value of sports diplomacy as a complementary force to conventional diplomatic endeavors. The research aims to emphasize the influence of sports diplomacy on shaping international relations and propelling peace-building initiatives forward.